Representations of the world in language textbooks - Risager, Karen 1947- (Languages for intercultural communication and education, 2018)
"This book presents a new and comprehensive framework for the analysis of representations of culture, society and the world in textbooks for foreign and second language learning. It points to the need for language learning materials to deal seriously with knowledge about the world, including its diversities and problems"--Provided by publisher.